2003
DOI: 10.1128/aem.69.11.6946-6948.2003
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium xenopi and Drinking Water Biofilms

Abstract: The ability of Mycobacterium xenopi to colonize an experimental drinking water distribution system (a Propella reactor) was investigated. M. xenopi was present in the biofilm within an hour following its introduction. After 9 weeks, it was always present in the outlet water (1 to 10 CFU 100 ml ؊1 ) and inside the biofilm (10 2 to 10 3 CFU cm ؊2 ). Biofilms may be considered reservoirs for the survival of M. xenopi.Mycobacteria have no usual adherence factors such as pili, fimbriae, and slime, but the hydrophob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
19
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 13 publications
2
19
0
Order By: Relevance
“…This has also been demonstrated for species of Mycobacterium, which in our study increased from about 0.15% in raw water to around 0.3% in the filter (Table 1). Like Legionella, species of Mycobacterium are natural colonizers of BAC (Wang et al 2013), can survive within amoebae (Thomas et al 2008), and have been identified as a prevalent microbe in both experimental and treatment plant filters and distribution systems (Dailloux et al 2003;Revetta et al 2013;Revetta et al 2016;Stanish et al 2016;Thomas et al 2008;Wang et al 2013). Species of Mycobacterium are of particular concern for drinking water safety, given that they are the causal agent of human and animal van Hannen, E.J., Zwart, G., van Agterveld, M.P., Gons, H.J., Ebert, J., and Laanbroek, H.J.…”
mentioning
confidence: 99%
“…This has also been demonstrated for species of Mycobacterium, which in our study increased from about 0.15% in raw water to around 0.3% in the filter (Table 1). Like Legionella, species of Mycobacterium are natural colonizers of BAC (Wang et al 2013), can survive within amoebae (Thomas et al 2008), and have been identified as a prevalent microbe in both experimental and treatment plant filters and distribution systems (Dailloux et al 2003;Revetta et al 2013;Revetta et al 2016;Stanish et al 2016;Thomas et al 2008;Wang et al 2013). Species of Mycobacterium are of particular concern for drinking water safety, given that they are the causal agent of human and animal van Hannen, E.J., Zwart, G., van Agterveld, M.P., Gons, H.J., Ebert, J., and Laanbroek, H.J.…”
mentioning
confidence: 99%
“…Its survival in fl owing water systems and resistance to common disinfectants enables M. xenopi to contaminate laboratory samples and medical devices such as bronchoscopes, thus causing healthcare-acquired (pseudo) infections and laboratory cross-contaminations (3,6,8,9). Differentiating true infection from pseudoinfection is of paramount importance because treatment of M. xenopi infections is time-consuming and often complicated.…”
mentioning
confidence: 99%
“…However, a public health risk exists only if biofilm detachment leads to the release of entrapped pathogens that are still infectious. Although many studies on the interactions between drinking water biofilms and pathogenic bacteria have been carried out (3,6,9,12,37,53), little is known about the specific interactions of viruses with drinking water biofilms. In a review, Skraber et al (42) highlighted the lack of quantitative data that precludes concluding whether drinking water biofilms play a significant role or not in the fate of viruses.…”
mentioning
confidence: 99%